Gain-flattened fiber amplifier from 1560 to 1580 nm wavelengths using an erbium-doped fiber amplifier - Adikan, Faisal Rafiq Mahamd; Mahdi, M.A.; Poopalan, Prabakaran; Dimyati, Kaharudin; Ahmad, Harith (John Wiley & Sons, 2000)
A simple gain-flattened L-band erbium-doped fiber amplifier (EDFA) is demonstrated. An L-band flat gain range of 20 nm (1560-1580 nm) is achieved for use in wavelength-division multiplexing (WDM) transmission systems. Gain flatness with a 1 dB gain discrepancy is obtained through manipulation of the pump power, and no additional devices (gain equalizer, attenuator, fiber-Bragg grating) are required. (C) 2000 John Wiley & Sons, Inc.